Tiger Girls : Women and Enterprise in the People's Republic of China. - Chen, Minglu (Routledge studies on China in transition., 2011)
The last three decades in the People's Republic of China have been characterized by decentralization, marketization and privatization. What might be expected from a developing country like China with a significant number of women in the labour force? Do the traditional values of male superiority still stay the same in the background of China's great social change? The notion of 'tiger girls' seems to reflect one of the alternative paths that is now becoming available to the modern Chinese woman. The social development and changes in recent China have provided women with access to education, em.